Genre in a Changing World - Bazerman, Charles; Bonini, Adair; Figueiredo, Débora (Open textbook library., 2009)
Genre studies and genre approaches to literacy instruction continue to develop in many regions and from a widening variety of approaches. Genre has provided a key to understanding the varying literacy cultures of regions, disciplines, professions and educational settings. Genre in a Changing World,edited by Charles Bazerman, Adair Bonini, and Débora Figueiredo,provides a wide-ranging sampler of the remarkable variety of current work. The twenty-four chapters in this volume, reflecting the work of scholars in Europe, Australasia, North and South America, were selected from more than 400 presentations at SIGET IV (the Fourth International Symposium on Genre Studies), held on the campus of UNISUL in Tubarão, Santa Catarina, Brazil in August 2007—the largest gathering on genre to that date. The chapters also represent a wide variety of approaches including rhetoric, Systemic Functional Linguistics, media and critical cultural studies, sociology, phenomenology, enunciation theory, the Geneva school of educational sequences, cognitive psychology, relevance theory, sociocultural psychology, activity theory, Gestalt psychology, and schema theory. Sections are devoted to theoretical issues, studies of genres in the professions, studies of genre and media, teaching and learning genre, and writing across the curriculum. The broad selection of material in this volume displays the full range of contemporary genre studies and sets the ground for a next generation of work.